2007
DOI: 10.1002/adv.20100
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous rheological response for binary blends of linear polyethylene and long‐chain branched polyethylene

Abstract: ABSTRACT:The rheological properties are studied for binary blends composed of a low-density polyethylene (LDPE) and a linear polyethylene. It is found that some blends exhibit higher oscillatory shear moduli and drawdown force than the individual pure components, demonstrating that relaxation mechanism with longer characteristic time appears in the blend. The anomalous rheological behavior is detected more clearly for the blends with autoclave-LDPE than those with tubular-LDPE. Furthermore, the number of short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…However, recent our work revealed that the number of short-chain branches in a linear polyethylene, which affects the miscibility as shown by Lohse et al from both theoretical and experimental approaches [18], has no/little influence on the anomalous rheological properties. Therefore, the blends with an ethylene-butene-1 copolymer (LLDPE) having a lot of shortchain branches (36 branches per 1000 backbone carbon atoms) show almost the same rheological properties as the blends with HDPE as far as the shear viscosity of the HDPE is the same level of the LLDPE [11,17,19]. The synergetic properties were observed irrespective of the mixing method.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, recent our work revealed that the number of short-chain branches in a linear polyethylene, which affects the miscibility as shown by Lohse et al from both theoretical and experimental approaches [18], has no/little influence on the anomalous rheological properties. Therefore, the blends with an ethylene-butene-1 copolymer (LLDPE) having a lot of shortchain branches (36 branches per 1000 backbone carbon atoms) show almost the same rheological properties as the blends with HDPE as far as the shear viscosity of the HDPE is the same level of the LLDPE [11,17,19]. The synergetic properties were observed irrespective of the mixing method.…”
Section: Introductionmentioning
confidence: 72%
“…Furthermore, even LLDPE produced by metallocene catalyst having significantly narrow molecular weight distribution can enhance the drawdown force, defined as the force required for stretching a polymer melt, of LDPE [14][15][16]. Moreover, the anomalous rheological properties are marked for the blends with LDPE having well developed branch structure [10,17]. According to Wagner et al [8], phase separation is the origin of the enhanced melt elasticity.…”
Section: Introductionmentioning
confidence: 94%
“…Accordingly, the blends are declared to be thermorheologically simple. Master curves of frequency dependence of shear storage modulus G′ and loss modulus G′′ for a couple of blends of linear and branched polyethylene, plotted using horizontal shifts and without any vertical ones, were investigated by Mieda and Yamaguchi [7]. They reported that all the blends showed thermorheological simplicity.…”
Section: Master Curvesmentioning
confidence: 98%
“…However, rather similar physical properties of components make some difficulties in study of the melt of a blend, and the phase behavior of many common binary blends, such as ones composed of a low-density polyethylene (LDPE) and a high-density polyethylene (HDPE), is not fully understood yet [5][6][7]. Rheological responses of polymeric melts are of importance since they are not only sensitive to molecular structure but also to phase behavior [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…4,5,[11][12][13][14][15][16][17][18] Several studies have shown that ethylene polymerizations with combinations of different catalysts and variations of the polymerization processes can produce reactor blends with improved physical and/or chemical properties. 1,4,5,[11][12][13][19][20][21][22] In most of the early reports, metallocene catalysts such as titanium, zirconium, and hafnium compounds were the main choices for catalyst combinations. 11,23,24 Some catalysts combined in a polymerization reactor have been successful in producing ethylene homopolymer independently, 5,[15][16][17] and this suggests that the active sites are not affected by interactions between the different site types present in the polymerization mixtures.…”
Section: -10mentioning
confidence: 99%